High-Temperature Induced Changes of Extracellular Metabolites in Pleurotus ostreatus and Their Positive Effects on the Growth of Trichoderma asperellum - Qiu, Zhiheng; Wu, Xiangli; Zhang, Jinxia; Huang, Chenyang (Frontiers in Microbiology, 2018)
Pleurotus ostreatus is a widely cultivated edible fungus in China. Green mold disease of P. ostreatus which can seriously affect yield is a common disease during cultivation. It occurs mostly after P. ostreatus mycelia have been subjected to high temperatures. However, little information is available on the relationship between high temperature and green mold disease. The aim of this study is to prove that extracellular metabolites of P. ostreatus affected by high temperature can promote the growth of Trichoderma asperellum. After P. ostreatus mycelia was subjected to high temperature, the extracellular fluid of P. ostreatus showed a higher promoting effect on mycelial growth and conidial germination of T. asperellum. The thiobarbituric acid reactive substance (TBARS) content reached the maximum after 48 h at 36 °C. A comprehensive metabolite profiling strategy involving gas chromatography-mass spectrometry (GC/MS) combined with liquid chromatography-mass spectrometry (LC/MS) was used to analyze the changes of extracellular metabolites in response to high temperature. A total of 141 differential metabolites were identified, including 84.4 % up-regulated and 15.6 % down-regulated. Exogenous metabolites whose concentrations were increased after high temperature were randomly selected, and nearly all of them were able to promote the mycelial growth and conidial germination of T. asperellum. The combination of all selected exogenous metabolites also has the promotion effects on the mycelial growth and conidial germination of T. asperellum in a given concentration range in vitro. Overall, these results provide a first view that high temperature affects the extracellular metabolites of P. ostreatus, and the extensive change in metabolites promotes T. asperellum growth.